Bending and looping of long DNA by Polycomb repressive complex 2 revealed by AFM imaging in liquid. Issue 6 (11th February 2020) - Heenan, Patrick R; Wang, Xueyin; Gooding, Anne R; Cech, Thomas R; Perkins, Thomas T
Abstract: Polycomb repressive complex 2 (PRC2) is a histone methyltransferase that methylates histone H3 at Lysine 27. PRC2 is critical for epigenetic gene silencing, cellular differentiation and the formation of facultative heterochromatin. It can also promote or inhibit oncogenesis. Despite this importance, the molecular mechanisms by which PRC2 compacts chromatin are relatively understudied. Here, we visualized the binding of PRC2 to naked DNA in liquid at the single-molecule level using atomic force microscopy. Analysis of the resulting images showed PRC2, consisting of five subunits (EZH2, EED, SUZ12, AEBP2 and RBBP4), bound to a 2.5-kb DNA with an apparent dissociation constant ($K_{\rm{D}}^{{\rm{app}}}$ ) of 150 ± 12 nM. PRC2 did not show sequence-specific binding to a region of high GC content (76%) derived from a CpG island embedded in such a long DNA substrate. At higher concentrations, PRC2 compacted DNA by forming DNA loops typically anchored by two or more PRC2 molecules. Additionally, PRC2 binding led to a 3-fold increase in the local bending of DNA's helical backbone without evidence of DNA wrapping around the protein. We suggest that the bending and looping of DNA by PRC2, independent of PRC2's methylation activity, may contribute to heterochromatin formation and therefore epigenetic gene silencing.